Justiça nos trilhos: redes comunicativas de comunidades e movimentos sociais em defesa das atingidas e dos atingidos pela Vale S.A. na Amazônia - SANTOS, Larissa Pereira (Universidade Federal do Pará, 2020)
The present work aims to analyze the Justice On the Rails Network as a network of communities and social movements that act in defense of the women and men affected by the Vale S.A. corporation on the Amazon. We begin with the hypothesis that the Justice On the Rails is a communicative articulation of communities and social movements that develops activities in the physical and virtual spaces to denounce impacts and to promote rights through local, national and international actions. The network was first created in 2007 as an international campaign to seek support for the people hit by the Vale S.A. and has gained adherence of various social movements, communities, syndicates, and organizations during the World Social Forum (WSF), in 2009, in Belém of Pará, Brazil. We took as the basis the following question: How do Justice On the Rails articulations occur among different communities and social movements to stand against the actions of the Vale S.A.? Other questions also make themselves necessaries: What are their objectives? What social actors make part of the network? What are the communication processes that can be seen face to face and on the Internet as network articulation? In search of answers, we have engaged with the theoretical contributions of Freire (1983), Wolton (2010), Gohn (2013, 2014), Scherer-Warren (2006, 2011), Castells (2013, 2015), Melucci (1989), Tourraine (1989, 1998), Pinsky e Pinsky (2013), Mouffe (2003, 2015), Buber (1982), Peruzzo (2005, 2009, 2013, 2017), Paiva (2011) e Amorim (2018), among others, to understand the studies about social movements, social movements network, forms of social mobilizations, collective actions, communication, citizenship and community. The methodology consists of a qualitative-descriptive approach, alongside with the use of Content Analysis to study Justice On the Rails forms of organization on the Internet. As techniques we used wheels of conversations, participant observation, followed by open and semistructured interviews at the Meeting of Youth Affected by Mining (Maranhão), at the Regional Meeting of People Affected by Mining (Pará and Maranhão), and at the Exhibition and Cycle of Debates “From the river which was sweet to the other side of the rails, the irreversible mining damage” (Pará), to understand their networks of communities and social movements. The meetings occurred on June, July and August 2017. During June and July 2017 we also monitored the Justice On the Rails’ social media and website, with the intention to perceive the network articulations manifested in the internet. We consider that the Justice On the Rails communicative networks are processes developed in the scope of communitarian, alternative, popular and dialogic communication, having the transformation of the communities affected by Vale S. A. as an central objective, for which they help in the construction and expansion of citizenship through developing their practices on social media or on the Internet.